2022
DOI: 10.3389/fmicb.2022.933941
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Dynamics in Kumamoto Oyster Crassostrea sikamea Hatchery During Larval Development

Abstract: Increasing evidence indicates that microbes colonized in early life stages have a long-term effect on animal wellbeing in later life stages. Related research is still limited in aquatic animals, particularly in bivalve mollusks. In this study, we analyzed the dynamics of the bacterial composition of the pelagic larval stages (fertilized egg, trochophore, D-stage, veliger, and pediveliger) and the sessile postlarval stage (spat) of Kumamoto oyster (Crassostrea sikamea) and their relationships with the rearing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
2
1
0
Order By: Relevance
“…The decrease in the abundances of these known probiotics may have a negative effect on oyster larval growth. Additionally, we observed that Proteobacteria was the most abundant phylum in Kumamoto oyster larvae, which was consistent with the previous reports on the larval microbiome of Kumamoto oyster and eastern oyster [8,31]. It is well known that most members of Proteobacteria are pathogenic, especially Vibrio species [2].…”
Section: Discussionsupporting
confidence: 91%
“…The decrease in the abundances of these known probiotics may have a negative effect on oyster larval growth. Additionally, we observed that Proteobacteria was the most abundant phylum in Kumamoto oyster larvae, which was consistent with the previous reports on the larval microbiome of Kumamoto oyster and eastern oyster [8,31]. It is well known that most members of Proteobacteria are pathogenic, especially Vibrio species [2].…”
Section: Discussionsupporting
confidence: 91%
“…The results suggest that host development may lead to a more dispersed gut bacterial community. This result was steady with previous research, which reported that development could lead to a more mature and complex host gut microbiota, and the more mature the organism, the greater the differences in individual microbial community structure [54,66,67]. Therefore, we concluded that the host was uncovered to microbial successions during ontogeny.…”
Section: Discussionsupporting
confidence: 89%
“…Epidemiological investigation of hatchery epidemics indicated that Ostreid herpesvirus 1 (OsHV-1), Vibrio algniolyticus, Vibrio mediterranei, and Pseudoalteromonas spp. were the potential pathogenic microorganisms [6][7][8][9]. The poor facilities to eliminate pathogens from seawater, poor biosecurity concepts during the operation, and management were assumed to be responsible for the insufficiency of disease prevention [6,10].…”
Section: Introductionmentioning
confidence: 99%